Consensus Statement of the Academy of Nutrition and Dietetics/American Society for Parenteral and Enteral Nutrition: Indicators Recommended for the Identification and Documentation of Pediatric Malnutrition (Undernutrition). (February 2015) - Becker, Patricia; Carney, Liesje Nieman; Corkins, Mark R.; Monczka, Jessica; Smith, Elizabeth; Smith, Susan E.; Spear, Bonnie A.; White, Jane V.; ,; ,
The Academy of Nutrition and Dietetics (the Academy) and the American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.), utilizing an evidence-informed, consensus-derived process, recommend that a standardized set of diagnostic indicators be used to identify and document pediatric malnutrition (undernutrition) in routine clinical practice. The recommended indicators include z scores for weight-for-height/length, body mass index-for-age, or length/height-for-age or mid–upper arm circumference when a single data point is available. When 2 or more data points are available, indicators may also include weight gain velocity (<2 years of age), weight loss (2–20 years of age), deceleration in weight for length/height z score, and inadequate nutrient intake. The purpose of this consensus statement is to identify a basic set of indicators that can be used to diagnose and document undernutrition in the pediatric population ages 1 month to 18 years. The indicators are intended for use in multiple settings (eg, acute, ambulatory care/outpatient, residential care). Several screening tools have been developed for use in hospitalized children. However, identifying criteria for use in screening for nutritional risk is not the purpose of this paper. Clinicians should use as many data points as available to identify and document the presence of malnutrition. The universal use of a single set of diagnostic parameters will expedite the recognition of pediatric undernutrition, lead to the development of more accurate estimates of its prevalence and incidence, direct interventions, and promote improved outcomes. A standardized diagnostic approach will also inform the prediction of the human and financial responsibilities and costs associated with the prevention and treatment of undernutrition in this vulnerable population and help to further ensure the provision of high-quality, cost-effective nutritional care.